The controversial role of human chorionic gonadotropin in the development of breast cancer and other types of tumors. (April 2016) - Gehring, Caroline; Siepmann, Timo; Heidegger, Helene; Jeschke, Udo
Abstract: Introduction: Breast cancer is the most often diagnosed tumor of women and one of the leading cause of cancer related death. Due to different known risk factors there are epidemiological differences. Beside genetic disorders and patient's age it is especially the age of the first full-term pregnancy and in this context the pregnancy hormone human chorionic gonadotropin that seems to play an important role. Methods: This review is based on a PubMed research in publications of the last 20 years. Only articles in English language were considered. Results: The effect of human chorionic gonadotropin on development of cancer is controversial. In fact, for breast cancer there is evidence that this hormone has a protective effect against tumorigenesis due the differentiation of the mammary tissue after a full term pregnancy through the downregulation of estrogen receptors. Conclusion: Human chorionic gonadotropin has among promoting pregnancy important controversial functions especially in tumor development. The mechanisms that explain the pro- and anti-carcinogenic effects are not fully understood yet. It seems to have a protective effect on breast cancer through increasing differentiation and hereby decreasing susceptibility of the mammary tissue for toxicants. This knowledge might help developing a preventive agent in the next future that uses the anti-carcinogenic effect of human chorionic gonadotropin and thereby decrease the mortality out of breast cancer. Highlights: HCG can have procarcinogenic and anticarcinogenic effects on tumorigenesis. Trough hCG the risk of development of breast cancer seems to decrease. HCG leads to an increase in differentiation of the mammary tissue. Anti-hCG vaccines could potentially decrease mortality of breast cancer in future.